Mental Disorders Related to Stroke - Puszkarz, Irena; Guty, Edyta; Stefanska, Iwona (Journal of Education, Health and Sport, 2018)
Stroke is third most common cause of death and the most common reason for disability in people over 45 years old. It impacts people in social and economic aspects. As a result of stroke, patients struggle to function in everyday life, they often require rehabilitation as they are limited in the way they can move. Experts reckon that the most serious complications after stroke are problems with cognitive functions and depression (1). Very often there is more attention paid to deficit of mobility or speech than cognitive function problems or depression. Stupor occurs in 1/3 of patients that experienced stroke.